(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1873)
The article begins by describing the location and dimensions of a souterrain found near Dundee. The author then goes on to discuss the finds that were uncovered at the site and their significance. He also highlights some other prehistoric monuments in the area and the history of the church at Tealing.